Computer Virus: Their Problems & Major at-tacks in Real Life - Joshi, Milind. J.; patil, Bhaskar Vijayrao (Journal of Advanced Computer Science & Technology, 2012)
Today's enterprise networks are distributed to different geographical locations and applications are more centrally located, information represents the most important asset. With the growing number of data communication services, channels and available software applications, data are processed in large quantities and in a more efficient manner. This technological enhancement offers new flexible opportunities also measure security threats poses in the networks. These threats can external or Internal, external threats divided as hacking, virus attack, Trojans, worms etc. There are thousand and thousand of different viruses these days which improve every day. Although the wild spread of new and strong viruses, it still infects and spread only with user's permission. This research paper highlights the phases of computer virus, computer virus, history of worst computer attack, type of computer virus with effect on computer & few examples of virus on their types, working of computer virus, and problem occur due to virus in computers.